Rheological, textural and microstructural features of probiotic whey cheeses - Madureira, A. Raquel (2012)
Whey cheeses have been manufactured with probiotic bacteria e viz. Bifidobacterium animalis Bo and Lactobacillus casei LAFTIrL26, from combinations of bovine whey and milk, following protein denaturation at 90 ºC; they were subsequently inoculated (at 10%) with those strains, and homogenized afterwards; additives such as salt and sugar were then incorporated; and the resulting solid matrices were stored at 7º C for up to 21 d. Oscillatory measurements and instrumental texture profile analyses were performed, and sensory analyses were carried out by a trained panel. Microstructural features were in addition ascertained by scanning electron microscopy. L. casei exhibited a higher acidifying activity than B. animalis, which produced distinct textures; higher firmness and viscoelasticity were indeed found in matrices inoculated with the former. Incorporation of sugar and L. casei favoured consumer acceptability, relative to plain matrices. Microstructural differences were detected between matrices at different times of storage and formulated with distinct additives.